PENINGKATAN KUALITAS SEMANGKA DENGAN ZAT PENGATUR TUMBUH GIBERELIN - ACHMAD FATCHUL AZIEZ; AGUS BUDIYONO; ADI PRASETYO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
The aim of this research is to know the effect of giberelin on the quality of watermelon fruit, fruit weight, fruit diameter, fruit flesh diameter, and number of seeds per fruit. The research conducted in March to June 2018, in Donoyudan village, Kalijambe district, Sragen regency. This study used a factorial method with the basic design of a Completely Randomized Block Design consisting of two treatments and three replications: 1 Gibberellin concentration: G0 = 0 ml / l water, G1 = 5 ml / l water, G2 = 10 ml / l water, G3 = 15 ml / l water, G4 = ml / l water, 2. Application Time: F1 = 07.00 - 08.00, F2 = 16.00 - 17.00. The results showed that the highest watermelon weight was obtained by giving 5 ml / l of gibberellin which was applied in the morning and lowest with no gibberellin application.